Evaluation of the performance of the national zakat agency (BAZNAS) using financial ratios for optimization - Wijayanti, Lulud (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2025)
As the coordinator of zakat management institutions in Indonesia, BAZNAS has undertaken various efforts to enhance performance. However, the overall performance of zakat management organizations (OPZ) remains suboptimal. A precise and timely performance analysis method is needed to evaluate OPZ comprehensively and identify priority areas for improvement. To address this, BAZNAS has developed a financial ratio analysis as a tool to measure the performance and sustainability of non-profit zakat organizations, consisting of the activity ratio, efficiency ratio, amil fund ratio, liquidity ratio, and growth ratio. Therefore, this research aims to analyze the performance of BAZNAS using special financial ratios for Zakat Management Institutions. This research uses a descriptive method with a quantitative approach, namely by describing the financial performance of BAZNAS over the last five years by first determining the financial ratios for non-profit institutions and then comparing them between years. This type of research data is secondary data, namely the audited financial reports of BAZNAS for 2018-2022. The results of this research state that BAZNAS' financial performance is declared optimal based on the activity ratio and amil fund ratio, while the other 3 ratios (efficiency ratio, liquidity ratio and growth ratio) state that BAZNAS' performance is not good.